Unravelling Malaria Antigen Binding to Antibody‐Gold Nanoparticle Conjugates. (25th October 2016) - Cavadas, Miguel A. S.; Monopoli, Marco P.; Cunha, Cláudia Sá e; Prudêncio, Miguel; Pereira, Eulália; Lynch, Iseult; Dawson, Kenneth A.; Franco, Ricardo
Abstract : Conjugates formed by antibody adsorption to gold nanoparticles (AuNP) have found extensive utilization in immunoassays due to the high surface area and interesting optical and electronic properties of the nanomaterials. Nevertheless, the mechanism of formation of antibody‐AuNP conjugates and their antigen binding characteristics have not been sufficiently explored in terms of specificity and consequent clinical applicability. Dynamic light scattering and related techniques have been successfully employed to detect antigen binding to antibody‐AuNP complexes. Here, a range of different techniques from the bionanotechnology realm have been applied to obtain a detailed picture of a competitive immunoassay for malaria antigen detection, based on fluorescence‐quenching by AuNPs. Both agarose gel electrophoresis and differential centrifugal sedimentation (DCS) analyses provide binding constants in the same order of magnitude, for antibody binding to AuNP and for antigen binding to antibody‐AuNP conjugates. Both techniques are also able to reveal inhibition of antigen binding in the presence of a major blood plasma protein, transferrin (via competitive binding). DCS is further used to show inhibition of the binding of the antigen in the presence of human plasma, a realistic testing condition, of high relevance to the implementation of immunoassays at the clinical level. Abstract : To elucidate the mechanism of formation of antibody‐AuNP conjugates and their antigen binding characteristics, agarose gel electrophoresis and differential centrifugal sedimentation are applied to an immunoassay for malaria antigen detection. Binding constants for antibody binding to AuNP and for antigen binding to antibody‐AuNP conjugates are obtained. Antigen binding is inhibited in the presence of transferrin, or of human plasma.